Evaluation of students' attitudes towards pharmacist-physician collaboration in Brazil - Prado FO; Rocha KS; Araújo DC; Cunha LC; Marques TC; Lyra DP Jr (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Objective. To measure undergraduate pharmacy and medical students' collaborative attitudes regarding Pharmacist-Physician collaboration. Methods. A cross-sectional descriptive study was conducted from September 2016 to February 2017 in Northeast Brazil. Pharmacy and medical students from the first and the last year of courses were invited to complete Portuguese version of Scale of Attitudes Toward Pharmacist-Physician Collaboration (SATP2C). Descriptive and comparative analyses were performed using IBM SPSS (22 version). Differences were considered significant when p<0.05. Results. Three hundred seventy students completed the SATP2C. Overall, the students had positive attitudes towards physician-pharmacist collaboration. There was no significant correlation between age and score (p=0.79). Women showed a more positive collaborative attitude than men (53.1, SD=6.8 vs. 55.1, SD=6.3). Pharmacy students had a higher score than medical students (57.5, SD=4.7, vs. 51.1, SD=6.4). The first-year medical students had a higher score than last-year medical students (52.3, SD=6.0 vs. 49.5, SD=6.6; p<0.007). There was no significant difference in the attitudes between the first and last year pharmacy students (p<0.007). Conclusions. Pharmacy and medical students showed positive attitudes towards physician-pharmacist collaboration. However, pharmacy students presented more collaborative attitudes than medical ones. Additionally, the first-year medical students had more collaborative attitudes than last-year medical students. Studies should be conducted to provide recommendations to improve interprofessional education efforts to further enhance the positive attitudes toward physician-pharmacist collaboration.